A 4-DoF Pick-and-Place Robot With High Structural Rigidity and Pose Repeatability - Ming-Yang Cheng; Hao-Chun Liao; Chao-Chieh Lan (IEEE Access)
Parallel robots can use large actuators fixed to the base to provide larger driving torque without affecting the moving inertia. Hence, parallel robots are suitable for picking and placing large payloads at high speeds. For pick-and-place applications to be productive, a parallel robot must exhibit high pose repeatability and short stabilization time. This paper investigates the structural compliance, dynamics, and control of a new Schönflies-motion parallel robot. The aim is to achieve high-speed and large-payload motion with high pose repeatability and short stabilization time. Using a novel kinematic chain to achieve limb symmetry, the compliance distribution of the robot can be homogeneous in the workspace. The exclusive use of revolute joints can eliminate joint clearance issues and make the robot stronger. Experimental results are presented to verify the high structural rigidity of the robot in all directions. Asymmetric jerk profiles are proposed to significantly reduce the residual vibration during the stopping motion. Experiments on stabilization time, pose repeatability, and large payloads are given to show the merits of the parallel robot over existing counterparts. The pose accuracy can also be greatly improved through kinematic calibration. The outcomes suggest that this new parallel robot can advance pick-and-place automation.